Enriching the formalism of coloured Petri nets for modelling alternative structural configurations of a discrete event system: disjunctive CPN. (2017) - Latorre-Biel, Juan Ignacio; Parte, Mercedes Pérez De La; Jiménez-Macías, Emilio
Discrete event systems (DESs) provide an approximate approach for dealing with certain types of real systems. DES has been extensively and successfully used in modelling and simulation of technological systems and processes. In this field, coloured Petri nets (CPNs) have arisen as a practical formalism for modelling discrete event systems, widely used thanks to the easiness of their application, as well as the compactness of the resulting models, and the availability of computer software, ready to be used for modelling, simulation, theoretical analysis, as well as performance evaluation. This paper derives from the CPN, a formalism focused on modelling discrete event systems with alternative structural configurations. That is to say, systems with freedom degrees in their structure, which should be solved by decision-makers, deducing the best configuration among a set of alternative structures.